SRATEGI PEMENUHAN KEBUTUHAN KELUARGA PETANI SAWIT DALAM MENGHADAPI FLUKTUASI HARGA KELAPA SAWIT DI DESA BEBATUNG KABUPATEN LANDAK - Elsa, Elsa; Mashudi, Mashudi; Syamsuri, Syamsuri (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2025)
The purpose of this study was to analyze the strategy of fulfilling the needs of oil palm farmer families in facing fluctuations in palm oil prices in Bebatung Village, Landak Regency. This study uses a qualitative approach with a descriptive type of research. Data collections and are carried out in there ways, namely interviews, observations and dokumentations, involving oil palm farmers in Bebatung Village. The results of this study indicate that the strategis used to fulfill the needs of oil palm farmer families in facing fluctuations in palm oil prices in Bebatung Village are: When the price of palm oil is high, it has a positive impact on the economic canditions of households, a sense of security, clam and being able to meet the management and increased saving. When the price of palm oil is low a) Implementing a frugal lifestyle; b) Carrying out stricter financial planning; c) Saving; d) Utilizing Natural Resources in the from of gardening, framing rice; e) Looking for additional sources of income, namely opening a barber shop, selling snacks or snacks, opening a grocery business or grocery stall, working as a carpenter, becoming a casual laborer and tapping rubber.